Aspects of trees and their influence in reducing solar radiation penetration to the ground - Abu Bakar, Aniza; Abdul Malek, Nurhayati; Mohamad, Amira Nadhirah; Mohd. Ariffin, Noor Aziah (2013)
Vegetation plays an important role in modifying the climate in urban areas. Apart from its function that is to provide shade, the absorption of high proportion of the solar radiation by the dark green leaves, the cooling effect from the evaporation of water from the leaves and the potential of reducing glare are among the roles of vegetation in modifying the microclimate. Not only providing the screening effect to reduce the solar penetration on the ground and walls, the existence of trees in clumps also has the potential in reducing the ambient temperature. However, the potential of trees in addressing the above mentioned functions are yet to be empirically investigated. This study is intended to investigate the aspect of trees: which are the trunk height, crown height, diameter of the canopy as well as the foliage density, and their effect in screening the solar radiation from penetrating and heating the ground. The data collection was done within the campus of the International Islamic University Malaysia (IIUM) due to the availability of various types of trees. Conducted in July 2013 this study involved 89 trees from four case study sites. Solar radiation readings were taken at human level of about 1.5m from the ground underneath the canopies of the investigated trees, between 11am to 3pm. The initial results show significant reduction of the quantity of solar radiation penetrating the canopies from the different tree aspects. These findings are hoped to guide designers in choosing appropriate trees in achieving their design intentions especially when addressing the thermal comfort of users and in mitigating the urban heat island effect.